2017
DOI: 10.1111/all.13261
|View full text |Cite
|
Sign up to set email alerts
|

ADAM10 and Notch1 on murine dendritic cells control the development of type 2 immunity and IgE production

Abstract: Targeting ADAM10 and Notch1 on DCs represent a novel strategy for modulating T 2 immune responses and IgE production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Notably, Notch signaling has been reported to be crucial during CD8α − cDC differentiation (23). Furthermore, a recent report that studied mice in which DC-specific depletion of ADAM10 revealed that ADAM10-mediated Notch signaling was crucial for TH2 allergic lung inflammation (24). However, the role of ADAM10 during cDC differentiation has yet to be elucidated.…”
Section: Significancementioning
confidence: 99%
“…Notably, Notch signaling has been reported to be crucial during CD8α − cDC differentiation (23). Furthermore, a recent report that studied mice in which DC-specific depletion of ADAM10 revealed that ADAM10-mediated Notch signaling was crucial for TH2 allergic lung inflammation (24). However, the role of ADAM10 during cDC differentiation has yet to be elucidated.…”
Section: Significancementioning
confidence: 99%
“…Targeting Notch1 signaling on DCs has been proposed as a novel strategy for modulating Th2 immune responses ( 31 ). So, we evaluated if Notch1 signaling was necessary for the LACK 156–173 epitope to polarize DCs, by using siRNA to silence Jagged1 expression in BMDCs, which were cultured from bone marrow cells of BALB/c mice.…”
Section: Resultsmentioning
confidence: 99%
“…Dendritic cell-specific ADAM10-knockout mice have been generated by crossing ADAM10 floxed mice with CD11c-Cre mice ( 62 ). These mice have strikingly impaired Th2 responses, but Th1 and Th17 responses are unaffected.…”
Section: Regulation Of Myeloid Cell Function By Adam10 and Potential mentioning
confidence: 99%
“…As a consequence, the mice are protected from IgE-mediated anaphylaxis and allergic lung inflammation. This appears to be due to defective Notch signaling, since rescue is observed by transgenic expression of the Notch1 intracellular domain, and dendritic cell-specific Notch1-knockout mice have a similar phenotype ( 62 ). Our RNA-Seq analyses have found Tspan14 to be most highly expressed in human dendritic cells, with lower expression of Tspan17 and Tspan33 (data not shown).…”
Section: Regulation Of Myeloid Cell Function By Adam10 and Potential mentioning
confidence: 99%